PENGARUH TUNJANGAN KINERJA, DAN WORK LIFE BALANCE TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PEGAWAI BAGIAN PENGADAAN BARANG/JASA SEKRETARIAT DAERAH KABUPATEN PASURUAN - Susiadi Hari Priyanto ,; Sundjoto, Sundjoto; Sri Rahayu , (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to examine and explain the impact of performance allowances and work-life balance on employee performance in the Procurement of Goods/Services Division at the Regional Secretariat of Pasuruan Regency, both directly and through job satisfaction. The study uses a sample of 95 employees from the Procurement of Goods/Services Division of Pasuruan Regency and employs a census research method. Data analysis is conducted using Partial Least Square (PLS) with a variance-based Structural Equation Modeling (SEM) approach, implemented through SmartPLS software to address normality issues and accommodate small sample sizes. The results indicate that performance allowances can enhance employee performance by reducing stress and fatigue-related boredom. Additionally, a good work-life balance contributes positively to employee performance, especially when employees can manage work and personal life demands. Performance allowances are proven to improve employee performance through increased job satisfaction, while work-life balance does not significantly contribute to performance through job satisfaction. This study provides insights into the importance of these factors in improving employee performance in the public sector.